A New Fern Species Of Hypodematium (Hypodematiaceae) From China (Bangladesh Journal of Botany, 2023)
Hypodematium jianxiuii is closer to Hypodematium sinense K. Iwats., but differs greatly from it which is illustrated and described by using LM and SEM characters. It differs mainly by its plant height along with laminae broad ovate-pentagonal, 40 × 40 cm, 4–pinnate. The lower part of the stalk and rachis of Hypodematium jianxiuii is nearly smooth; the middle and upper part of the rachis, the costae and the lower part of the laminae has glandular hairs and sparsely short acicular hairs, the upper part of the laminae is covered with short acicular hairs and sparsely covered with glandular hairs, the dorsal surface of the indusia are densely covered with short acicular hairs and sparsely covered with glandular hairs; and spore is reniform with tuberculate protrusions and granular ornamentation.Bangladesh J. Bot. 51(4): 943-949, 2022 (December) Special